2008
DOI: 10.1111/j.1439-0418.2008.01286.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of pheromone mimic to cause the disintegration and collapse of colonies of tent caterpillars (Malacosoma spp.)

Abstract: The disruption of the trail‐based communication system of eastern tent caterpillars (ETC) (Malacosoma americanum) and forest tent caterpillars (FTC) (M. disstria) by spraying host trees with a trail pheromone mimic caused the disintegration and collapse of young colonies. A 1‐ppm formulation of 5β‐cholestan‐3‐one or a control formulation was sprayed on trees either before or after eclosion of the caterpillars in the spring. For pre‐eclosion trials, an average of 92% of the FTC colonies on control trees, but on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…In contrast to studies with ants, the results reported here for C. cactorum, and a previous study of tent caterpillars (Fitzgerald 2008), indicate that trail marking caterpillars are more vulnerable to colony collapse when their trail systems are disrupted. For the 4 experiments reported here, the average survivorship of C. cactorum larvae from colonies on cladodes sprayed with mandibular gland pheromone was approximately 15% compared with 80% on unsprayed control plants.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to studies with ants, the results reported here for C. cactorum, and a previous study of tent caterpillars (Fitzgerald 2008), indicate that trail marking caterpillars are more vulnerable to colony collapse when their trail systems are disrupted. For the 4 experiments reported here, the average survivorship of C. cactorum larvae from colonies on cladodes sprayed with mandibular gland pheromone was approximately 15% compared with 80% on unsprayed control plants.…”
Section: Discussioncontrasting
confidence: 99%
“…As with C. cactorum, new eclosed caterpillars of both tent caterpillar species dispersed independently instead of aggregating en masse on their egg mass, their normal behavior. Although specific causes of C. cactorum larval loss in our study were not determined, tent caterpillar larvae typically perished by losing purchase on the branches of the host tree and falling to the ground (Fitzgerald 2008). A previously reported laboratory study suggested that falls from the plant also may constitute a major mortality factor for C. cactorum (Fitzgerald et al 2016).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Tent caterpillars travelled in parades around the arena floor. Applications of synthetic trail pheromone disrupts social cohesion of young caterpillars, but was not repellent (Fitzgerald 2009). Thus, repellency of our test materials appears to override such signals.…”
Section: Social Caterpillarsmentioning
confidence: 97%
“…Aggregation pheromones, for example, play an important role in sustaining insect attack and infestation levels (Hughes 1974;Silverstein 1981;Wood 1982;Vité and Baader 1990;Schlyter et al 2001), especially of bark beetles. Sex pheromones have also been widely used for mass trapping and mating disruption to suppress various pests, especially relevant to the Lepidoptera (Fitzgerald 2008;Norin 2001;Thorpe et al 1999;Silverstein 1981). Research on plant-derived semiochemicals such as volatile organic compounds can aid in plant protection but are often less specific and can be complex to dissect and apply.…”
Section: Analysis Of Semiochemical Researchmentioning
confidence: 99%